2009
DOI: 10.1063/1.3207751
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of the current leakage in charge ordered Lu2Fe2Fe1−xMnxO7 (<x≤0.86)

Abstract: The ferroelectricity, magnetic properties, and charge-ordering modulations in the layered Lu2Fe2Fe1−xMnxO7 have been investigated for x ranging from 0 to 0.86. Experimental measurements reveal that substitution of Mn for Fe could evidently influence the low temperature magnetic transition. Moreover, ferroelectric analysis suggests that introduction of Mn ions in this layered system can efficiently suppress the conducting leakage and result in clear hysteresis loops in the polarization–electric field switching … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 16 publications
(12 reference statements)
1
19
0
Order By: Relevance
“…TEM investigations also reveal that this transition is reversible, though remarkable hysteresis often exists, the superstructure reflections become visible again as the temperature is lowered below the critical temperature. Figure 3f shows a typical diffraction pattern taken from a Lu 2 Fe 2 Fe 0.2 Mn 0.86 O 7 sample that shows a clear hysteresis loop in the polarization-electric field switching curves [18]. Like Lu 2 Fe 3 O 7 , the superstructure spots can be similarly assigned to the incommensurate q 1 and q 2 modulations.…”
Section: Charge Ordered States In Lumentioning
confidence: 95%
See 2 more Smart Citations
“…TEM investigations also reveal that this transition is reversible, though remarkable hysteresis often exists, the superstructure reflections become visible again as the temperature is lowered below the critical temperature. Figure 3f shows a typical diffraction pattern taken from a Lu 2 Fe 2 Fe 0.2 Mn 0.86 O 7 sample that shows a clear hysteresis loop in the polarization-electric field switching curves [18]. Like Lu 2 Fe 3 O 7 , the superstructure spots can be similarly assigned to the incommensurate q 1 and q 2 modulations.…”
Section: Charge Ordered States In Lumentioning
confidence: 95%
“…In our recent study, we performed systematic measurements of the polarization switching in Lu 2 Fe 2 Fe 1-x Mn x O 7 samples with x ranging from 0 to 0.86. The experimental results demonstrate that the current leakage can be significantly suppressed in the samples as the Fe is partially replaced by Mn [18]. Figure 2e shows a hysteresis P-E loop taken at room temperature, illustrating the ferroelectric nature of the Lu 2 Fe 2 Fe 0.2 Mn 0.86 O 7 material.…”
mentioning
confidence: 86%
See 1 more Smart Citation
“…12,13 One effective approach to suppress the current leakage is to introduce carrier doping and intercalated layers. 14,15 The intercalation of FeO 1.5 single layer (V layers) into between two Fe 2 O 2.5 double layers (W layers), i.e., the compound Lu 2 Fe 3 O 7 (the inset in Fig. 1), is an effective approach to tune the dielectric properties and magnetism in this family; furthermore, it has been found that Mn doping can reduce the conductivity and thus improve the ferroelectric property in Lu 2 (Fe,Mn) 3 O 7 .…”
Section: O 7 I Introductionmentioning
confidence: 98%
“…Li et al [15] have reported the decrease of bulk conductivity in Mn-doped CaCu3Ti4O12. Qin et al [16] have reported that the introduction of Mn ions into Lu2Fe2Fe1-xMnxO7 can efficiently suppress the electrical conducting leakage. After analyzing the relationship between the electrical resistivity and Mn 3+ content in La0.7Ca0.3MnO3 thin films, De Teresa et al [17] found that the polaron binging-energy is proportional to the Mn-O octahedral distortion.…”
Section: A Introductionmentioning
confidence: 99%